Recent Advances in Theory and Methods for the Analysis of High Dimensional and High Frequency Financial Data - Swanson, Norman R.; Yang, Xiye (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Recently, considerable attention has been placed on the development and application of tools useful for the analysis of the high-dimensional and/or high-frequency datasets that now dominate the landscape. The purpose of this Special Issue is to collect both methodological and empirical papers that develop and utilize state-of-the-art econometric techniques for the analysis of such data.